2006
DOI: 10.1002/uog.2728
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine therapy for preterm labor: effects on placental, fetal cerebral and atrioventricular Doppler parameters in the first 48 hours

Abstract: Objective To assess the effect of nifedipine tocolysis on Doppler parameters of the uterine, umbilical and fetal middle cerebral arteries and atrioventricular valves in the first 48 h of therapy. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 59 publications
4
33
2
1
Order By: Relevance
“…In contrast to our findings, Guclu et al detected significant fall in uterine artery pulsatility index at 24 and 48 h of tocolysis. 16 Similar to our findings they showed no changes in the blood flow in umbilical artery (RI and PI) at the same point of time.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to our findings, Guclu et al detected significant fall in uterine artery pulsatility index at 24 and 48 h of tocolysis. 16 Similar to our findings they showed no changes in the blood flow in umbilical artery (RI and PI) at the same point of time.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have investigated the possible effects of nifedipine on fetomaternal blood flow . Two previous studies reported that nifedipine does not cause a significant change in uteroplacental and fetal Doppler parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported significantly decreased pulsatility and resistance indices of the fetal middle cerebral artery in the first 24-48 h after tocolysis with nifedipine [10,26]. However, Verhagen et al [24] and Grzesiak et al [27] did not find an effect of nifedipine on neonatal cFTOE or fetal CBF, respectively.…”
Section: Discussionmentioning
confidence: 99%